GOD WHO SAW ME: FAITH AND DEHUMANIZATION OF EXEGESIS STUDIES GENESIS 16 - Irawati, Chandra Wahyuni (QUAERENS: Journal of Theology and Christianity Studies, 2022)
The story of Abram and Sarah is an interesting story to discuss. Chaotic household trips due to the issue of Sarah's infertility became a crucial problem that saddened both of them. In the ancient world, Sarah's barrenness was not only considered a disgrace in the family, but also a serious problem for Abram as a man who would have no heir. Impatience awaits offspring, and Sarah's suggestion for Abram to take Hagar turns out to be a domestic conflict and oppression of Hagar, the servant. But God's grace did not only apply to Abram and Sarah but also to Hagar.